Antireflux surgery in patients with moderate obesity: fundoplication or roux-en-Y gastric bypass? - Betzler, Johanna; Wiegand, Nina; Kantorez, Alexandra; Finze, Alida; Schölch, Sebastian; Reißfelder, Christoph; Otto, Mirko; Blank, Susanne (Obesity surgery, 2025)
Gastroesophageal reflux disease (GERD), often associated with obesity, impairs quality of life and can lead to complications. This study compared Fundoplication and Roux-en-Y Gastric Bypass (RYGB) in patients with WHO (World Health Organization) class I and II obesity and refractory GERD.
Online veröffentlicht: 27. März 2025
Gesehen am 12.06.2025